Economics of the public sector (Larsen and Keller Education, 2018)
Public economics refers to the process of using fields like equity and economic efficiency to study the importance and use of government policy and interference of government in economic markets. The most important topics included in this field are analysis of market, government failure, public finance, taxation and its effects, public policy design, etc. While understanding the long-term perspectives of the topics, the text makes an effort in highlighting their impact as a modern tool for the growth of the discipline. This textbook is a complete source of knowledge on the present status of this important field. It is meant for students who are looking for an elaborate reference text on public economics.